Effect of nonenzymatic deamidation on the structure stability of Camelus dromedarius α-lactalbumin. (1st September 2019) - Si Ahmed Zennia, Saliha; Mati, Abderrahmane; Charron, Christophe; Cakir-Kiefer, Céline; Kriznik, Alexandre; Girardet, Jean-Michel
Highlights: Camelids' α-lactalbumin can undergo nonenzymatic deamidation on two Asn residues. X-ray crystallography shows that deamidation might induce formation of a short extra α-helix. Deamidation reinforced the thermostability of the α-lactalbumin and resistance to proteolysis. The generation of a mixture of unusual isoAsp andd -Asp residues may impact health. Abstract: Camelid α-lactalbumin is the only known protein that can undergo nonenzymatic deamidation on two Asn residues. This leads to the generation of a mixture of unusual isoAsp andd -Asp residues that may impact health. The effect of deamidation on camel α-lactalbumin instability was investigated. Circular dichroism showed that the altered protein acquired secondary structure resulting in an increase in α-helix content. In good agreement, the 3D structure of camel α-lactalbumin determined by X-ray crystallography, displayed a short additional α-helix probably induced by deamidation, compared to the human and bovine counterparts. This α-helix was located in the C-terminal region and included residues 101–106. Differential scanning calorimetry together with the susceptibility to thermolysin showed that the deamidation process reinforced the structural stability of the α-lactalbumin at high temperature and its resistance toward proteolysis.